Extension agents or agents of change?. Issue 1 (May 2015) - COLVIN, CHRISTOPHER J.; SWARTZ, ALISON; Maes, Kenneth
<x xml:space="preserve">Abstract</x> Global public health discourse and practice around community health workers (CHWs) often invoke two distinct ideal types: the CHW as an "extension agent" of biomedical health services, bringing health services into community and household settings, and the CHW as a progressive "agent of change, " working with communities to mobilize socially and politically around health inequities and identify and tackle the social determinants of health. In this article, we examine the experience of postapartheid South Africa with CHWs and take a critical look at the degree to which these conventional models of CHWs account for how CHWs in South Africa have emerged, what kinds of work they have done, how they have organized themselves, and what impacts they have had. In the end, we argue that these two models miss much of what is interesting and important about the lives and work of CHWs in South Africa. We further make the case that both mainstream and progressive public health academics and activists tend too often to frame—and reify—CHWs as a much‐anticipated solution to a variety of (much bigger) health system and political problems. We maintain, instead, that to adequately understand and support the work of CHWs, one must begin by situating community‐based care work within a much broader analysis of these problems.